Rituximab for antibody-negative combined central and peripheral demyelination presenting with acute respiratory failure: a case report and literature review - Zheng, Yuanjiang; Hou, Jiangyan; Jiang, Youjun; Yu, Jianglin; Zhang, Ni; Ye, Xianwei (Frontiers in Immunology, 2025)
Antibody-negative combined central and peripheral demyelination (CCPD) is a rare neuroimmunological disorder with heterogeneous manifestations and variable treatment response. We report a case of a 40-year-old man who developed acute hypercapnic respiratory failure following influenza A infection. Neuroimaging revealed demyelinating lesions in the brainstem and spinal cord, and nerve conduction studies showed multifocal peripheral demyelination. Peripheral immune profiling demonstrated marked B-cell activation and elevated serum interleukin-6 (IL-6). The patient responded poorly to corticosteroids, intravenous immunoglobulin, and plasma exchange, but improved rapidly after two consecutive daily doses of 100 mg rituximab (RTX), which was accompanied by a significant reduction in IL-6 levels, CD19+ B-cell depletion, ventilator weaning, and marked neurological recovery. This case underscores the importance of considering neuroimmunological causes in acute hypercapnic respiratory failure of unclear etiology. The close temporal association between IL-6 decline, B-cell depletion, and clinical improvement suggests that the B-cell–IL-6 axis may play a central role in antibody-negative CCPD pathogenesis. Low-dose RTX may represent a safe and effective therapeutic option in refractory cases.